Assessing the Quality of Islamic Early Childhood Education: Evidence from Raudhatul Athfal’s Compliance with National Standards in Bandung - Masnipal; Tri Yugo (Program Studi Pendidikan Islam Anak Usia Dini, Fakultas Ilmu Tarbiyah dan Keguruan, UIN Sunan Kalijaga, Yogyakarta, 2025)
The quality assurance of early childhood education in Islamic institutions such as Raudhatul Athfal (RA) has received limited empirical attention, particularly regarding the extent to which they fulfill the National Standards for Early Childhood Education. This study seeks to fill this gap by evaluating the learning quality of RA institutions in Baleendah District. Using a descriptive quantitative approach, data were collected from 50 RA educators through a validated and reliable Likert-scale questionnaire measuring eight dimensions of the national standards. Descriptive statistical analysis was employed to calculate the percentage of achievement for each dimension. The findings indicate that overall learning quality in RA has met national standards, with notable strengths in exploration-based learning, collaborative pedagogy, and parental involvement. However, challenges remain in cognitive stimulation, the pedagogical competence of educators, and the adequacy of exploratory and extracurricular facilities. Limited funding emerged as a key barrier, constraining infrastructure development and teacher professional growth. Beyond its national relevance, this study contributes to the broader global scholarship on early childhood education by demonstrating how faith-based institutions operationalize educational quality within diverse cultural and moral frameworks. The findings enrich international understanding of how holistic and value-oriented learning can coexist with standardized educational benchmarks. This study introduces a perspective of contextualized quality, emphasizing that true educational excellence is achieved when pedagogical competence, moral education, and local wisdom are integrated into a coherent framework. Practically, it provides policy insights for strengthening teacher capacity, improving learning environments, and promoting collaborative engagement among stakeholders. Future studies are encouraged to adopt mixed-method and comparative approaches to deepen cross-cultural insights into the dynamics of early childhood education quality in Islamic contexts.